RISK MANAGEMENT IN OIL & GAS FIELD DEVELOPMENT PROJECT WITH MARGINAL RESOURCES: A CASE IN A MATURE FIELD IN EAST KALIMANTAN - Ayusta Saptarini, Dyah
The oil and gas industry and risks are very related to each other. Several risks are known in this industry, from economic, political, environmental and safety, up to geological risk itself. Because oil and gas are non-renewable source of energy, the more mature an oil and gas field is, the risks for the company to develop a project investment may be lower and higher at the same time. Entering its declining phase, PT MNO who is trusted to operate an ex-termination oil and gas field in East Kalimantan which has been producing for almost 50 years, is required to find a way to survive until the end of the contract in 2037 by developing the remaining hydrocarbon resources which become more and more marginal. The project development is proposed as bundling to allow flexibility during the execution phase in selecting the well candidates based on recent data acquired from previous wells drilled, hence reducing the risks. Field Development Package (FDP) 2.3 is prepared as part of PT MNO’s long-term plan and commitment after receiving incentives from the Government of Indonesia in 2021. According to the Company Guideline, a risk register is mandatory to be developed since beginning of the project which covers risks identification, risks analysis, and risks evaluation. The project team is also responsible to define risk treatment to manage the risks borne by the project. This is in line with the requirement for Good Corporate Governance, where risk management is introduced at beginning of the project life-cycle. This study covers the risk assessment on the basis of the selected project scope which has been validated technically. The risk assessment will determine the most important risks in FDP 2.3 considering the internal factors including core competencies in subsurface, drilling, and well connection as well as external factors such as oil price trends and gas/ LNG demand. These risks need to be monitored to ensure the FDP 2.3 will create value for the shareholder as per plan, avoid losses, or seize opportunities. The risk analysis will be based on Focus Group Discussion with the company expert and use the Analytical Hierarchy Process (AHP) with Expert Choice. Additional risk treatments are proposed for the risk events classified as moderate to high risks. The implementation plan has been proposed to address these risks, completed with action plan, entity in charge (risk owner), timeline, type of record, and the strategy involved. This study suggested that for development of oil and gas mature field with marginal resources, the most important risks are related to oil/gas price movement, technical subsurface data, gas commercialization scheme, drilling cost overrun, delay in procurement, and global gas/ LNG demand. The company may focus in these risks for the risk management of future project development.